Expectations of Indian guests from hotel preparedness in COVID-19 / Sarah Hussain, Firdous Ahmad Shah and Saima Kareem - Hussain, Sarah; Ahmad Shah, Firdous; Kareem, Saima (Faculty of Hotel & Tourism Management, 2020)
Covid-19 brought the entire world and economies to a sudden halt. To contain the spread of Covid-19, implementation of lockdown and travel restrictions have adversely affected the tourism and hospitality sector. Unless the guest expectations during this contagion are not gauged and reported swiftly, the hotels will not attract the business back timely. This study aims to evaluate the factors that influence the expectations of Indian guests regarding safety measures in hotels as a consequence of the COVID-19 pandemic. The data was collected using a structured questionnaire with many open-ended questions to draw meaningful responses. The findings revealed that Indians would consider using hotels for their accommodation purpose during travel, but they have a few expectations and suggestions concerning their stay at the hotels. The study has revealed preferences for hotel categories for stay considering COVID-19 preparedness. The guests expect the hotels to follow stringent safety measures from different departments of hotels elaborated in this paper. The study proposes several practical implications for managers to acclimate for the COVID-19 recovery.